AB1305 Risk of autoimmune rheumatic diseases in patients with palindromic rheumatism: a nationwide, population-based, cohort study. (12th June 2018) - Chen, H.-H.; Chao, W.-C.; Liao, T.-L.; Lin, C.-H.; Chen, D.-Y.
Abstract : Background: Although the association between palindromic rheumatism (PR) and rheumatoid arthritis (RA) development has been widely reported, no research has estimated the magnitude of the risk of progression of PR to RA or to other autoimmue rheumatic diseases, such as systemic lupus erythematosus (SLE), systemic sclerosis (SSc), Sjogren's syndrome (SS), dermatomyositis (DM) and polymyositis (PM). Objectives: This study aimed to examine the relative risk of development of RA, SLE, SSc, SS, DM, or PM among patients with PR compared with that in non-PR individuals using a nationwide, population-based, administrative dataset. Methods: The study utilised 2003–2013 claims data from the Taiwanese National Health Insurance Research Database. We identified 4421 cases of PR from 2007 to 2012 and randomly chose 44 210 non-PR individuals who matched (1:10) for age, sex and the year of index date without prior history of RA, SLE, SSc, SS, DM, or PM. After adjusting for age, sex, and the Charlson comorbidity index, we calculated the hazard ratios (HRs) with 95% confidence intervals (CIs) using the Cox proportional hazard model to quantify the risk of RA, SLE, SS, DM and PM in PR patients compared with that in matched non-PR individuals. Results: Tthe mean age ±SD was 46±15 years, and 70.4% of the study subjects were female. The proportion of patients with one or more CCI was higher in the PR group than in the non-PR group (33.0% vs. 14.8%, p<0.001). Among the 4421 patients with PR, 569 (12.87%) developed RA, 269 (6.08%) developed SS, 113 (2.56%) developed SLE, 5 (0.11%) developed SSc, 8 (0.18%) developed PM, and 1 (0.02%) developed DM. After adjusting for potential confounders, the patients with PR had an increased risk of RA (HR, 118.76; 95% CI, 89.81–157.04), SS (HR, 59.57; 95% CI, 43.87–80.88), SLE (HR, 51.56; 95% CI, 32.96–80.66) PM (HR, 57.38; 95% CI, 6.90–476.83), and SSc (HR, 13.42; 95% CI, 3.79–47.55) but not of DM (HR, 3.44; 95% CI, 0.34–34.59). Conclusions: Patients with PR had an increased risk of developing RA, SS, SLE, PM, and SSc. References: [1] Gonzalez-Lopez L, Gamez-Nava JI, Jhangri GS, Ramos-Remus C, Russell AS, Suarez-Almazor ME. Prognostic factors for the development of rheumatoid arthritis and other connective tissue diseases in patients with palindromic rheumatism. The Journal of rheumatology. 1999;26(3):540–5. PubMed PMID: 10090159. [2] Sanmarti R, Canete JD, Salvador G. Palindromic rheumatism and other relapsing arthritis. Best practice & research Clinical rheumatology. 2004;18(5):647–61. doi: 10.1016/j.berh.2004.05.005. PubMed PMID: 15454124. Acknowledgements: The authors would like to thank the Biostatistics Task Force of Taichung Veterans General Hospital, Taichung, Taiwan, ROC for statistical support. Disclosure of Interest: None declared